Proving a radio frequency based system to determine performance in sports - Kempe, M.; Scholz, S.; Richter, K.; Hökelmann, A. (World Congress of Performance Analysis of Sport VIII, 2008)
In the literature you won`t find any information about the required accuracy for such kind of a measurement system. However Hökelmann and Blaser (2007) demanded a minium CEP between 200 an 300 mm to observe movements in gymnastics. This would fit to the calculated CEP95 (26,95mm) which shows, in combination with the marginal dynamic deviation (0,27%), the excellent practicability of the system for indoor measurements. Other advantages are the large area the system covers (max 500x500m) and to get the information in real time so that coaches can interact immediately. Thus we should proceed by testing the system in the context of other sports for example ball games and in expending the existing Software tool.